The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1152/japplphysiol.00336.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses to ozone are increased in obese mice

Abstract: Epidemiological data indicate an increased incidence of asthma in overweight adults and children. Ozone (O3) is a common trigger for asthma. Accordingly, the purpose of this study was to compare O3-induced airway hyperresponsiveness and airway inflammation in lean, wild-type (C57BL/6J) mice and mice that are obese as a consequence of a genetic defect in the gene encoding the satiety hormone leptin (ob/ob mice). The ob/ob mice eat excessively and weighed more than twice as much as age- and gender-matched wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
230
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(261 citation statements)
references
References 63 publications
20
230
1
7
Order By: Relevance
“…A similar result was found in the Normative Aging Study (9). Several experimental studies in mice have identified augmented responses to ozone in obese animals (26,27). A recent experimental study in mice found that adiponectin, which is deficient in the obese, protects against the inflammatory effects of ozone exposure (31).…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found in the Normative Aging Study (9). Several experimental studies in mice have identified augmented responses to ozone in obese animals (26,27). A recent experimental study in mice found that adiponectin, which is deficient in the obese, protects against the inflammatory effects of ozone exposure (31).…”
Section: Discussionmentioning
confidence: 99%
“…Largely through the work of Shore et al, molecular and physiologic characteristics of the murine model of obese asthma are currently being elucidated. 23,[26][27][28][29][30][31][32][33][34] However, assessing lung inflammation and lung responses among obese children remains challenging and limited by current technologies. Studies in children involving bronchodilator responsiveness, bronchoconstricting agonists (e.g., methacholine challenge), and airway inflammatory markers have yet to show the same consistent pattern of hyperresponsiveness that have been demonstrated in mice.…”
Section: If Obesity Leads To Asthma What Is the Mechanism?mentioning
confidence: 99%
“…Further evidence of a direct association between obesity and airway hyperreactivity has been shown in an experimental study in which ozone-induced airway hyperreactivity and bronchial inflammation in obese mice were more pronounced than that observed in lean wild-type mice. 53 Obesity generally increases the production of estrogens, which are associated with early menarche in girls and delayed puberty in boys. 54,55 In the Tucson cohort, CastroRodriguez et al 56 observed the prevalence of asthma to be greater among obese girls with early menarche (before 11 years of age) than among those with later menarche.…”
Section: Potential Mechanisms Of Obesity-asthma Relationshipmentioning
confidence: 99%